Environmental management practices for the sustainable development of a new city in Mozambique - Bettencourt Coutinho, Pedro; Silva, Nuno; Fulgêncio, Cláudia; Canas, Ângela; Alcobia, Sónia (Brazilian Journal of Operations & Production Management, 2018)
Careful urban planning is of extreme importance in Mozambique, a developing country with a fast-growing population. Strategic Environmental Assessment (SEA) and Environmental and Social Impact Assessment (ESIA) are environmental management tools that can greatly benefit the planning process of sustainable urban spaces. This paper presents the contribution of SEA and ESIA to the environmental management of a new city in Mozambique, south of the Capital, Maputo, in the Katembe District. Katembe City’s environmental impact assessment process highlighted the particularities of this territory and identified the critical constraints for urban development and the requirements for minimization and monitorization of adverse impacts. The assessment process was developed sequentially, from a regional level to a local urban section level. In the preliminary assessment, major potential negative impacts were avoided and specific environmental and social detailed studies were defined, to be addressed in detailed urban plans. Following this, the detailed plans included all the necessary environmental requirements to avoid and mitigate several negative impacts, such as flooding, coastal erosion, biodiversity loss and habitat fragmentation. This case study emphasized the importance of SEA and ESIA in the planning process of the new city, resulting in a more sound and sustainable urban project.